Electrophysiological correlates of masked repetition and conceptual priming for visual objects - Li, Bingbing (Brain Behav, 2019)
BACKGROUND: Previous studies have investigated the time course of visual object processing using event‐related potential (ERP) and the masked repetition priming paradigm. However, it is unclear how the ERP correlates associated with masked repetition priming differentiate from masked conceptual priming of visual objects. METHOD: The present study used semantically related picture pairs of visual objects to compare the ERPs associated with masked repetition and conceptual priming of visual objects. RESULTS: The results revealed that masked repetition priming was associated with N/P190 and N400 effects, whereas masked conceptual priming was only associated with N400 effect. Moreover, the topography of repetition N/P190 effect was different from repetition and conceptual N400 effects, whereas the topography of repetition N400 effect was similar to conceptual N400 effect. CONCLUSIONS: These results indicated that masked repetition and conceptual priming were associated with spatiotemporally different ERP effects and that the N400 of visual objects was sensitive to automatic semantic spreading.